PENGGUNAAN STRATEGI EKSPOSITORI PADA PEMBELAJARAN MUSIK TRADISIONAL MINANGKABAU DI SMA NEGERI 3 PADANG - Sozy Randa; Jagar Lumbantoruan; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2018)
Abstract The study was aimed to know the use of principles which were done by using expository strategy on Minangkabau traditional music in SMA Negeri 3 Padang. The study was classified in qualitative research with descriptive approach. Instrument of the study was the researcher and assisted by some tools such as stationery, camera and audio recorder. Technique of data collection were done by doing observation, interviews, library reserach and documentation. Results of the study showed that in curriculum 2013, expository learning strategy was still eligible to be used, if the teachers could meet the criteria of the strategy of expository and they did not only focus on methods lecture and dictation. Criteria which should be met were preparation before the study began and conveyed the purpose of the study. Then in the presentation, the teachers should paid attention to the use of language such as used variety in teaching, designed learning messages, kept the voice intonation and kept contact with the students so that the students could focus on the taught material. In SMA Negeri 3 Padang, the art and cultural teachers were lack of understanding to principles of the expository learning strategy, the teachers more focused on the lecture and dictation only. Keywords : Expository Strategy, learning, Traditional music